THE EFFECT OF E-LEARNING ON STUDENTS SPEAKING SKILL PROGRESS: A CASE OF THE SEVENTH GRADE AT SMP PENCAWAN MEDAN - Rahmawati Rahmawati; Chanji Sihombing; Elya Karnela Br Ginting; Elfrida Arimonnaria (University of Kuningan, 2021)
This study aims to see whether e-learning has an effect on the progress of students' speaking skill and know the process of students' speaking skill in e-learning. This research uses quantitative methods with a descriptive approach. The study population was SMP Pencawan Medan with a sample of seventh grade of junior high school students. The data was collected by first explaining the recorded material orally through the WhatsApp group which contained 20 students and after that the students collected the audio of their voice by recording. The results of this study indicate that in seventh grade student s at SMP PENCAWAN MEDAN who can understand 20 students who have experienced a decreasing in speaking during face to face leaning before pandemic than e-learning from the score table during the pandemic, from the table of score during the pandemic, there were 2 students with excellent categories, no students with nice category, 8 students with the sufficient categories and 10 students with the not satisfactory categories. The researchers find some problems, namely in pronunciation, fluently, vocabulary and accuracy. When in e-learning process, students become embarrassed to speak and become lazy to speak English, then there is a decreasing in vocabulary, a decreasing in pronunciation and a decreasing in students' speaking fluency and accuracy.Keywords: E-learning; speaking skills; progress.